Approaches to eradicate absolute poverty in Guangdong Province, the People’s Republic of China - Wu, Jinhua; Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
Guangdong is the largest province by gross domestic product in the People's Republic of China. It faces remaining challenge on how the gains from absolute poverty eradication and rural revitalization will address relative poverty. The paper proposes the direction for the next steps.
Basic Economic and Social Indicators of Guangdong Province - - Overview of Poverty Reduction in Guangdong Province - - Important Measures by Finance Departments in Guangdong Province to Lift the Poor People out of Poverty - - Guangdong’s Experiences in the “Blood-Forming Type” of Poverty Alleviation - - Challenges and Pathways to Poverty Reduction - - Appendixes.
Keywords: Poverty -- China .; Sustainable development -- China; China -- Economic conditions .